Association of the Serum Folate and Total Calcium and Magnesium Levels Before Ovarian Stimulation With Outcomes of Fresh In Vitro Fertilization Cycles in Normogonadotropic Women - Polzikov, Mikhail; Blinov, Dmitry; Barakhoeva, Zarema; Vovk, Lyudmila; Fetisova, Yulia; Ovchinnikova, Maria; Tischenko, Marina; Zorina, Irina; Yurasov, Vasily; Ushakova, Tatyana; Sergeyev, Oleg (Frontiers in Endocrinology, 2022)
Background: Women of reproductive age are recommended to consume folic acid and other supplements before conception and during pregnancy. We aimed to investigate the association of the serum folate and magnesium (Mg) and calcium (Ca) levels before ovarian stimulation with the outcomes of assisted reproductive technology (ART) in normogonadotropic women. Methods: We used a subanalysis of data obtained from a multicentre, randomized prospective study (NCT03088137). A total of 110 normogonadotropic, non-advanced aged, non-obese women with tubal and/or male infertility factors were enrolled for the single fresh ovarian stimulation GnRH antagonist cycle. The main outcome measures were the total oocyte yield, mature oocytes, fertilization rate, biochemical, clinical pregnancy, and live birth. Multivariable generalized linear models adjusted for covariates were used with a Poisson distribution and the log link function for oocyte counts, and a binomial distribution and the log link function were used for clinical ART outcomes. Results: The medians (interquartile range (IQR)) were as follows: baseline serum folate, 20.55 ng/ml (10.8, 32.9); Mg, 19.4 mg/L (18.7, 20.7); Ca, 94 mg/L (91.2, 96.4); and Ca/Mg ratio, 4.78 (4.55, 5.02). Women with higher serum folate concentrations (Q4≥33.0 ng/ml) had significantly lower total numbers of oocytes retrieved (adjusted mean (95% CI) 9.2 (7.6-11.3) vs 12.9 (10.9-15.4, p-trend=0.006)) and lower odds ratios (ORs) (95% CI) of 0.12 (0.02, 0.79) for clinical pregnancy and 0.10 (0.01, 0.70) for live birth compared with women in the lowest quartile (<10.8 ng/ml), all p-trend<0.001. Women in the highest Ca/Mg ratio quartile (≥5.02) had ORs (95% CI) of 6.58 (1.31, 33.04) for biochemical pregnancy, 4.85 (1.02, 23.08) for clinical pregnancy and 4.07 (0.83, 19.9) for the live birth rate compared with women in the lowest quartile (<4.55), all p-trend<0.001. Conclusions: Using multivariable models, we suggested that a baseline elevated serum folate level (≥33.0 ng/ml) and a lower Ca/Mg ratio were associated with worse ART outcomes in normogonadotropic women. Our findings might be useful for choosing safe dosages of folate, calcium, magnesium and complex supplementation for both fertile women and women undergoing infertility treatment. Further preconception large-scale studies with known micro- and macronutrient statuses of both parents are needed.